ARTIFICIAL INTELLIGENCE: LEGAL STATUS (IN TERMS OF EXISTING CONCEPTS) (TAMADDUN NURI JURNALI, 2025)
This article examines the question of determining the legal status of artificial intelligence (AI) from the perspective of existing concepts. The author analyzes four main concepts: “AI as an object of law”, “AI as an animal”, “AI as a legal entity”, and “AI as an electronic entity (agent).” It is proposed to distinguish the digital form of artificial intelligence from its material carrier and to consider AI as an object of law taking into account its specificity.